2015
DOI: 10.4236/ajps.2015.613208
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield and Protein Content of Brazilian Cowpea Genotypes under Diverse Ugandan Environments

Abstract: Twenty nine cowpea genotypes, including four Ugandan genotypes, were evaluated for grain yield, protein stability and adaptability under diverse environments in a randomized complete block design with three replications. The analysis showed that cowpea grain yield and protein content were significantly (P < 0.01) affected by genotypes (G), environments (E), and interaction (G x E). Genotypes C2T and C2I had the highest grain yield and protein content respectively, but both were only adapted to specific environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 19 publications
(23 reference statements)
2
29
0
1
Order By: Relevance
“…The results from the research performed by Bliss et al [25] also indicated a significant genotype by location interaction effect on protein content in cowpea. In addition, Ddamulira and Santos [26] found that protein content in cowpea was significantly affected by the interaction between genotype and environment. Our date support their conclusion, genotype and environment have their contribution to seed protein content in cowpea.…”
Section: Resultsmentioning
confidence: 99%
“…The results from the research performed by Bliss et al [25] also indicated a significant genotype by location interaction effect on protein content in cowpea. In addition, Ddamulira and Santos [26] found that protein content in cowpea was significantly affected by the interaction between genotype and environment. Our date support their conclusion, genotype and environment have their contribution to seed protein content in cowpea.…”
Section: Resultsmentioning
confidence: 99%
“…The dry grain protein concentration oscillates from 21 to 33% (Abudulai et al, 2016). It is well adapted to hectic environments where several crops fail to grow well (Bisikwa et al, 2014;Ddamulira et al, 2015). According to FAO, cowpea was cultivated on about 12.08 million hectare in Africa in 2016 with a total production of 5.83 million hectare in West Africa, predominantly in Nigeria, Niger, Burkina Faso, Mali and Senegal (FAOSTAT, 2018).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…The leaves and grain are important foods with protein contents of 27-43% in leaves and 21-33% in grain (Ddamulira et al, 2015;Abudulai et al, 2016). It is also used as a livestock fodder in West Africa and can account for more than 40% of the value of the crop in the Sahel (Kamara et al, 2012;Maman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is also used as a livestock fodder in West Africa and can account for more than 40% of the value of the crop in the Sahel (Kamara et al, 2012;Maman et al, 2017). Cowpea can have high levels of biological N fixation and is relatively tolerant of soil water deficits with wide adaptation (Bisikwa et al, 2014;Ddamulira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%